2017
DOI: 10.1021/acs.biochem.6b01166
|View full text |Cite
|
Sign up to set email alerts
|

Packaged and Free Satellite Tobacco Mosaic Virus (STMV) RNA Genomes Adopt Distinct Conformational States

Abstract: The RNA genomes of viruses likely undergo multiple functionally important conformational changes during their replication cycles, changes that are poorly understood at present. We used two complementary in-solution RNA structure probing strategies (SHAPE-MaP and RING-MaP) to examine the structure of the RNA genome of satellite tobacco mosaic virus inside authentic virions and in a capsid-free state. Both RNA states feature similar three-domain architectures in which each major replicative function – translatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 23 publications
(111 reference statements)
2
37
0
Order By: Relevance
“…Although such interactions did not ensure efficient packaging of the full-length capsid genome on their own, several rounds of mutagenesis and screening afforded nucleocapsids with substantially higher loading capacity, greater specificity, and enhanced cargo protection. Consistent with suggestions that RNA architecture plays important roles in controlling the assembly of natural viruses (24,25,32), protein-protein and protein-RNA interactions were simultaneously optimized by coevolution of the circularly permuted capsid subunit with its encoding RNA. The resulting constructs are reminiscent of plant satellite viruses like satellite tobacco necrosis virus, which also have RNA genomes that encode only capsid protein and depend on cognate helper viruses to complement other aspects of the viral life cycle (33).…”
Section: Discussionsupporting
confidence: 58%
“…Although such interactions did not ensure efficient packaging of the full-length capsid genome on their own, several rounds of mutagenesis and screening afforded nucleocapsids with substantially higher loading capacity, greater specificity, and enhanced cargo protection. Consistent with suggestions that RNA architecture plays important roles in controlling the assembly of natural viruses (24,25,32), protein-protein and protein-RNA interactions were simultaneously optimized by coevolution of the circularly permuted capsid subunit with its encoding RNA. The resulting constructs are reminiscent of plant satellite viruses like satellite tobacco necrosis virus, which also have RNA genomes that encode only capsid protein and depend on cognate helper viruses to complement other aspects of the viral life cycle (33).…”
Section: Discussionsupporting
confidence: 58%
“…Collectively, there is strong support, based on evolutionary pressure, secondary structure RINGs, or previous functional studies, for 22 of the 24 elements identified de novo as low-SHAPE/low-entropy elements ( Fig. 2 A and B, elements 1-9, 11-14, and [16][17][18][19][20][21][22][23][24].…”
Section: Conservation Of Secondary Structure Elements In Diverse Denv2mentioning
confidence: 79%
“…We recently developed a strategy called RING-MaP to detect nucleotides involved in through-space structural communication (10,16). Here RNA is modified by dimethyl sulfate such that each strand contains multiple structure-specific modifications.…”
Section: Nucleotide-resolution Structural Interrogation Of Authentic mentioning
confidence: 99%
“…The parallel development of computational methods for comparative and integrative analysis of probing data has made it possible to recover biological insights from data generated in these experiments ( 32 , 33 ). To date, large-scale structural information exists for three ssRNA positive sense viral genomes: hepatitis C virus (HCV) ( 34 ), human immunodeficiency virus ( 35 ), and tomato bushy stunt virus (TBSV) ( 36 ) as well as the satellite tobacco mosaic virus ( 37 , 38 ). By structurally characterizing large regions of viral genomes at once, potentially interesting structures can be discovered much more rapidly, and in the proper context.…”
Section: Introductionmentioning
confidence: 99%